2018
DOI: 10.3390/geosciences8100362
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Substellar Objects below the Deuterium Burning Mass Limit: Planets, Brown Dwarfs or What?

Abstract: Free-floating, non-deuterium-burning, substellar objects" are isolated bodies of a few Jupiter masses found in very young open clusters and associations, nearby young moving groups and in the immediate vicinity of the Sun. They are neither brown dwarfs nor planets. I look over their nomenclature, history of discovery, sites of detection, formation mechanisms and future directions of research. Most free-floating, non-deuterium-burning, substellar objects share the same formation mechanism as low-mass stars and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 329 publications
0
22
0
Order By: Relevance
“…Assuming a semimajor axis a = 215 au (projected separation) for the orbit, a combined mass of the central binary of M * = 1 M and M p = 20 M J (Ginski et al 2018), we obtain r Hill /3 = 13.2 au for CS Cha C. To estimate r Hill we used a distance of d = 165 pc to be consistent with Ginski et al (2018). We note that recent GAIA distance estimates place the Chameleon I star formation region at 179±10 pc (GAIA DR1, Voirin et al 2018) or even at 192±6 pc (GAIA DR2, Dzib et al 2018), whereas the distance derived from the parallax reported in the GAIA DR2 catalogue (Gaia Collaboration et al 2016, 2018Lindegren et al 2018) of CS Cha is d = 176 ± 1 pc. Anyway, such distance variations do not have a significant impact on our results because for larger distances r Hill would also increase and the resulting fluxes of the models would remain very similar (see also Fig.…”
Section: Cs Cha Companionmentioning
confidence: 95%
See 1 more Smart Citation
“…Assuming a semimajor axis a = 215 au (projected separation) for the orbit, a combined mass of the central binary of M * = 1 M and M p = 20 M J (Ginski et al 2018), we obtain r Hill /3 = 13.2 au for CS Cha C. To estimate r Hill we used a distance of d = 165 pc to be consistent with Ginski et al (2018). We note that recent GAIA distance estimates place the Chameleon I star formation region at 179±10 pc (GAIA DR1, Voirin et al 2018) or even at 192±6 pc (GAIA DR2, Dzib et al 2018), whereas the distance derived from the parallax reported in the GAIA DR2 catalogue (Gaia Collaboration et al 2016, 2018Lindegren et al 2018) of CS Cha is d = 176 ± 1 pc. Anyway, such distance variations do not have a significant impact on our results because for larger distances r Hill would also increase and the resulting fluxes of the models would remain very similar (see also Fig.…”
Section: Cs Cha Companionmentioning
confidence: 95%
“…In contrast to PMCs millimetre-dust emission was already detected around the free-floating planet-mass object OTS 44 (Bayo et al 2017). There are many more free-floating planet candidates (see Caballero 2018) but so far only a few of these candidates show indications of a CPD (see Bayo et al 2017). For our presented modelling approach the only significant difference compared to PMCs is that the size of CPDs around freefloating planets is not limited by the Hill radius as they do not orbit a star or brown dwarf.…”
Section: Pmcs Versus Free-floating Planet-mass Objectsmentioning
confidence: 98%
“…A new NIR astrometry mission would provide us with homogeneous, accurate, parallactic distances of a very large sample of both ultracool dwarfs in the solar neighbourhood and brown dwarfs in a larger number of young starforming regions and juvenile open clusters (e.g. ρ Ophiuchi, Orion Nebula Cluster, Pleiades) down to, perhaps, the deuterium-burning mass limit [43]. Such an unbiased sample of very low-mass stars and substellar objects with masses down to the planetary regime and with very different ages will offer a magnificent panorama of the bottom of the initial mass function, which is a topic in astronomy that triggers vigorous discussion (see for example [20]).…”
Section: Brown Dwarfsmentioning
confidence: 99%
“…The dividing line between giant planets and brown dwarfs is not a very sharply delineated one, as there has been much debate regarding the classification of objects with masses of ∼ 3-10 M J , where M J denotes the mass of Jupiter, and with effective temperatures < 500 K; these objects do not appear to possess the capacity for deuterium fusion (Caballero 2018). As some of the salient physical and chemical characteristics are similar across giant planets and cool brown dwarfs (Burrows et al 2001;Hubbard et al 2002;Helling & Casewell 2014;Bailey 2014;Marley & Robinson 2015), it is natural to inquire whether the atmospheres of brown dwarfs are conducive to the origin and sustenance of life.…”
Section: Introductionmentioning
confidence: 99%